Mitotic Exit in the Absence of Separase Activity - Lu, Ying (The American Society for Cell Biology, 2009)
In budding yeast, three interdigitated pathways regulate mitotic exit (ME): mitotic cyclin–cyclin-dependent kinase (Cdk) inactivation; the Cdc14 early anaphase release (FEAR) network, including a nonproteolytic function of separase (Esp1); and the mitotic exit network (MEN) driven by interaction between the spindle pole body and the bud cortex. Here, we evaluate the contributions of these pathways to ME kinetics. Reducing Cdk activity is critical for ME, and the MEN contributes strongly to ME efficiency. Esp1 contributes to ME kinetics mainly through cohesin cleavage: the Esp1 requirement can be largely bypassed if cells are provided Esp1-independent means of separating sister chromatids. In the absence of Esp1 activity, we observed only a minor ME delay consistent with a FEAR defect. Esp1 overexpression drives ME in Cdc20-depleted cells arrested in metaphase. We have found that this activity of overexpressed Esp1 depended on spindle integrity and the MEN. We defined the first quantitative measure for Cdc14 release based on colocalization with the Net1 nucleolar anchor. This measure indicates efficient Cdc14 release upon MEN activation; release driven by Esp1 in the absence of microtubules was inefficient and incapable of driving ME. We also found a novel role for the MEN: activating Cdc14 nuclear export, even in the absence of Net1.